Relationship Between Empowerment Level and Profile of Farm Women Attending Vocational Training Programme - Singh, Neha; Bhardwaj, Neelam; Amardeep, Amardeep; Jukaria, Sudha (Indian Journal of Extension Education, 2020)
Empowering women and reducing gender inequalities are one of the major components of development objectives. The present study was conducted in Bhimtal district of Nainital to study the, profile characteristics of farm women and their relationship with empowerment level as a result of vocational training programme. The findings of the study showed that, empowerment level was found to be influenced by their profile characteristics. Variables like age, land holding, and annual income etc. showed a non-significant association with empowerment level in both beneficiaries and nonbeneficiaries. The result also shows that empowerment had significant association with selected independent variables such as scientific orientation and risk orientation. Therefore, the concerned organizations and personnel may manipulate those characteristics for improving theÂ psychological, social, and economic empowerment of farmwomen